Narrow intermediate-depth seismogenic band related to flexural strain in relatively dry Peruvian flat slab - Lingci Zeng; Lingling Ye; Huajian Yao; Wei Liu; Daojun Si; Thorne Lay; Ting Yang (Communications Earth & Environment)
Abstract The distribution and rupture properties of intermediate-depth earthquakes (70–300 km) provide insights into the interior stress state of the subducting plate, its petrological composition, and the subduction history. Here we evaluate the kinematic spatio-temporal rupture evolutions of four M7+ intermediate-depth earthquakes beneath Peru between 1997 and 2021 using teleseismic waveforms, which reveal similar rupture behavior over a limited depth range within the flat-slab segment. The intermediate-depth seismogenic zone is confined within a narrow band ~20 km thick near the slab surface, as also found in Pampean and Mexican flat slabs, contrasting to the broader seismicity distributions in the adjacent normally-dipping segments. The elongated earthquake ruptures in flat slabs with few aftershocks and the narrow, sparse seismicity bands are attributed to flexure from along-dip slab steepening and limited dehydration reactions within relatively dry flat-slab segments. Conversely, the diffuse seismicity in adjacent normally-dipping segments is likely associated with more widespread dehydration reactions.